The Effect of Cashless Payment and the Amount of the Money Circulation on the Inflation Rate in Indonesia for the Period of 2018-2021 - Dwi Yanti Sahriana; Muhammad Yafiz; Khairina Tambunan (LPPM UIKA Bogor, 2022)
This study aims to determine the effect of cashless payments and the money supply on the inflation rate in Indonesia in the period 2018-2021. The independent variables used are cashless payment and the money supply. While the dependent variable used in this study is the inflation rate. The research data used is secondary data, namely the number of cashless payment transactions and the inflation rate whose data source comes from the official website of Bank Indonesia (BI) and the money supply whose data source comes from the official website of the Central Statistics Agency (BPS). This research data consists of 48 data in which the data used is monthly data. The research method used in this research is quantitative with a descriptive approach. The analytical technique used in this research is multiple linear regression analysis using SPSS Version 22.00 analysis tool. The results obtained in this study are simultaneously independent variables in the form of cashless payments and the money supply has an effect on the dependent variable, namely the inflation rate in Indonesia in the period 2018-2021. While partially, the independent variable in the form of cashless payments affects the inflation rate in Indonesia in the period 2018-2021 and the independent variable in the form of the money supply also affects the inflation rate in Indonesia in the period 2018-2021.